Unearthing the nature and interplay of quality and safety in construction projects: An empirical study - Love, Peter; Teo, P.; Morrison, J. (Elsevier BV, 2018)
© 2017 Elsevier Ltd Effective implementation of quality and safety management is essential for ensuring the successful delivery of construction projects. While quality and safety possess a symbiotic relationship, there have been limited empirical lines of inquiry that have examined the nature of interaction between these constructs. With this mind, quality and safety data derived from 569 construction projects are analyzed. Quality was examined through the lens of non-conformances (NCRs), and safety under the guise of incidents. The quantity, cost and type of NCRs experienced are analyzed (n = 19,314) as well as the type and number of safety incidents (n = 20,393) that occurred. Examples of quality and safety incidents that arose in ‘practice’ are used to provide a contextual backdrop to the analysis that is presented. The analysis revealed that NCRs (e.g. rework, scrap, and use-as-is) were positively associated with injuries (p < .01). Human error is identified as the primary contributor to quality and safety issues, but the organizational and project environment within which people work provides the conditions for them to occur; people make mistakes, but there is a proclivity for organizations to enable them to materialize and result in adverse consequences occurring.